The Natural History of Uterine Leiomyomas: Light and Electron Microscopic Studies of Fibroid Phases, Interstitial Ischemia, Inanosis, and Reclamation - Gordon P. Flake; Alicia B. Moore; Deloris Sutton; Grace E. Kissling; John Horton; Benita Wicker; David Walmer; Stanley J. Robboy; Darlene Dixon (Obstetrics and Gynecology International)
We propose, and offer evidence to support, the concept that many uterine leiomyomas pursue a self-limited life cycle. This cycle can be arbitrarily divided on the basis of morphologic assessment of the collagen content into 4 phases: (1) proliferation, (2) proliferation and synthesis of collagen, (3) proliferation, synthesis of collagen, and early senescence, and (4) involution. Involution occurs as a result of both vascular and interstitial ischemia. Interstitial ischemia is the consequence of the excessive elaboration of collagen, resulting in reduced microvascular density, increased distance between myocytes and capillaries, nutritional deprivation, and myocyte atrophy. The end stage of this process is an involuted tumor with a predominance of collagen, little to no proliferative activity, myocyte atrophy, and myocyte cell death. Since many of the dying cells exhibit light microscopic and ultrastructural features that appear distinct from either necrosis or apoptosis, we refer to this process as inanosis, because it appears that nutritional deprivation, or inanition, is the underlying cause of cell death. The disposal of myocytes dying by inanosis also differs in that there is no phagocytic reaction, but rather an apparent dissolution of the cell, which might be viewed as a process of reclamation as the molecular contents are reclaimed and recycled.